D-Lucky Edge Labeling of Strong and Weak Human Chain Networks. Issue 1 (January 2021) - Rajini Ram, G.; Hemalatha, S.; Anitha, K.
Abstract: In this paper, we introduce two human chain networks namely Strong human chain and weak human chain network. Also, we have determined the D-Lucky edge number of Strong human chain and Weak human chain networks. These two networks have various application in Bus topology.